Preparation of Fast Dissolving Tablet by Some Traditionally Used Medicinal Plants & Its Anti-arthritic Evaluation in FCA Induced Arthritis - Tiwari, Om Prakash (International Journal of Pharmaceutical & Biological Archive, 2017)
Aim- The aim of the study was to evaluate the anti-arthritic activity of fast dissolving tablet prepared by methanolic extract of some traditionally used medicinal plants for arthritis. Material & Methods- Fast dissolving tablet of methanolic extract of selected medicinal plants were prepared by using Crospovidone & Î²-cyclodextrin by kneading methods. F1 formulation was evaluated in FCA induced arthritis and various lysosomal enzymes i.e. Cathepsin-D, Î²-glucuronidase and Î² -N-acetyl glucosaminidase were estimated. Results- Treatment by F1 formulation showed a significant decrease in all lysosomal enzymes as compared to arthritic control. Prednisolone also showed highly significant effect on lysosomal enzymes when compared to arthritic control. Conclusion- The prepared herbal fast dissolving tablets shows good disintegration property and dissolution rate. From the results of the study, we may conclude that F1 formulation might be act on membrane stabilization and membrane stability modulating effect is an important mechanism of anti-arthritic activity.